Highly reflective optical nanocavities for structural coloration by combining broadband absorber and Fabry–Pérot effects. (23rd December 2020) - Rossi, Stefano; Jonsson, Magnus P
Abstract: Reflective structural colors are of interest for many applications as alternatives to dyes and pigments and many different solutions have been proposed. The ideal systems should provide high reflectance efficiency while keeping good chromaticity and offering tunability throughout the visible spectral range. It is challenging to achieve such combined features with a simple single structure. Here we address this challenge using a concept that combines the Fabry–Pérot effect with a broadband absorbing layer. Our easy-to-fabricate structures form highly reflective optical nanocavities with improved chromaticity throughout the visible compared with the two separate concepts. The addition of an additional cavity layer and a transparent top coating further improves the chromaticity and allows the formation of black surfaces.